Comparison of palm prints and foot prints amongst three generations of Malay race in Malaysia [electronic resource] - Roszaharah Yaacob, 1986- (2013)
Thesis (Sarjana Sains (Sains Forensik)) - Universiti Teknologi Malaysia, 2013